Mystery Zeta

Calculus Level 5

0 1 ln ( 1 x ) ln ( 1 + x ) x d x \large \int_0^1 \dfrac{ \ln(1-x) \ln(1+x) } x \, dx

If the value of the integral above is equal to a b ζ ( c ) -\dfrac ab \zeta (c) , where a , b a,b and c c are positive integers with a , b a,b coprime, find a + b + c a+b+c .

Notation : ζ ( ) \zeta(\cdot) denotes the Riemann zeta function .


The answer is 16.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Mark Hennings
Apr 21, 2016

Recalling the alternating Euler sum a h ( 1 , 2 ) = n = 1 ( 1 ) n 1 ( n + 1 ) 2 H n = 1 8 ζ ( 3 ) a_h(1,2) \; =\; \sum_{n=1}^\infty \frac{(-1)^{n-1}}{(n+1)^2}H_n \; = \; \tfrac18\zeta(3) we observe that n = 1 ( 1 ) n n 2 H n = 1 + n = 1 ( 1 ) n 1 ( n + 1 ) 2 H n + 1 = 1 + n = 1 ( 1 ) n 1 ( n + 1 ) 2 H n + n = 1 ( 1 ) n 1 ( n + 1 ) 3 = a h ( 1 , 2 ) + n = 1 ( 1 ) n n 3 = 1 8 ζ ( 3 ) 3 4 ζ ( 3 ) = 5 8 ζ ( 3 ) \begin{array}{rcl} \displaystyle \sum_{n=1}^\infty \frac{(-1)^n}{n^2}H_n & = & \displaystyle -1 + \sum_{n=1}^\infty \frac{(-1)^{n-1}}{(n+1)^2}H_{n+1} \\ & = & \displaystyle -1 + \sum_{n=1}^\infty \frac{(-1)^{n-1}}{(n+1)^2}H_n + \sum_{n=1}^\infty \frac{(-1)^{n-1}}{(n+1)^3} \; = \; a_h(1,2) + \sum_{n=1}^\infty \frac{(-1)^n}{n^3} \\ & = & \displaystyle \tfrac18\zeta(3) - \tfrac34\zeta(3) \; = \; -\tfrac58\zeta(3) \end{array} Since 0 1 x n 1 ln ( 1 x ) d x = m = 1 1 m 0 1 x n + m 1 d x = m = 1 1 m ( m + n ) = 1 n H n \int_0^1 x^{n-1}\ln(1-x)\,dx \; = \; -\sum_{m=1}^\infty \frac{1}{m}\int_0^1 x^{n+m-1}\,dx \; = \; -\sum_{m=1}^\infty \frac{1}{m(m+n)} \; = \; -\tfrac{1}{n}H_n for any n 1 n \ge 1 , we see that 0 1 ln ( 1 + x ) ln ( 1 x ) x d x = = n = 1 ( 1 ) n 1 n 0 1 x n 1 ln ( 1 x ) d x = n = 1 ( 1 ) n n 2 H n = 5 8 ζ ( 3 ) \int_0^1 \frac{\ln(1+x)\ln(1-x)}{x}\,dx \; = \; =\sum_{n=1}^\infty \frac{(-1)^{n-1}}{n}\int_0^1 x^{n-1}\ln(1-x)\,dx \; = \; \sum_{n=1}^\infty \frac{(-1)^n}{n^2}H_n \; = \; -\tfrac58\zeta(3) making the answer 5 + 8 + 3 = 16 5+8+3 = \boxed{16} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...